Mode Choice for Sea Transportation in Archipelagic Region: The Case of Kendari-Konawe Route in South East Sulawesi Province - Rudi Azis; Asrul Asrul; Risman Risman (The Institute for Research and Community Services, Institut Teknologi Bandung, 2016)
The connectivity between Kendari City and Konawe Kepulauan Regency has affected the development of both regions. The connectivity between those two regions consists only of sea transportation with two types of transportation mode. The purpose of this study is to observe the behavior of users of sea transportation mode and to analyze characteristics of users of wooden ships and ferries on the Kendari City - Konawe Kepulauan Regency route, based on the preferences of passengers on the variety of attraction of the two modes. In this study, the characteristic of the selection of the sea transportation modes influences the total of traffic in the connection of both regions. The research design of this study is a modeling approach using a binomial logit model and a sample of 90 respondents. The results show that travel cost accounts for the difference in model utility which influences the selection of sea transportation modes for the two regions. Based on the perception of users, for ferries the purpose of trip is mostly for work while for wooden ships the purpose is mostly social. The reasons for selecting wooden ships are a variety of time and trip frequency, whereas the reason for selecting ferries is the cost.